2013
DOI: 10.1080/00220388.2012.700398
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disasters, Human Development and Poverty at the Municipal Level in Mexico

Abstract: This paper analyses the effects of natural disasters on human development and poverty levels at the municipal level in Mexico. Using several sources, we build a panel of data in order to uncover if different natural shocks can affect social indicators. After controlling for geographic and natural characteristics which can make municipalities more hazard prone, as well as for other institutional, socioeconomic and demographic pre-shock characteristics, in addition to using fixed effects, we find that general sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(85 citation statements)
references
References 17 publications
3
78
0
4
Order By: Relevance
“…For example, according to the multi-country analysis of Bergholt (2010), hydrometeorological events such as floods, wet mass movements and storms would reduce short term growth more than geophysical disasters like earthquakes and volcano eruptions (-0.5% and -0.1% respectively). Similarly, Rodriguez-Oreggia et al (2010) analyzing the case of Mexico, found that on average droughts would reduce the human development index by 1.3% while other disasters (avalanche, eruption, hailstorm, surge, snowstorm, earthquake, electric storm, tornado and strong winds) would reduce it by 1.0%. We classified the disasters in three broad categories, the third one accounting for non-natural disasters that were included in the analyses.…”
Section: Disaster Typementioning
confidence: 99%
“…For example, according to the multi-country analysis of Bergholt (2010), hydrometeorological events such as floods, wet mass movements and storms would reduce short term growth more than geophysical disasters like earthquakes and volcano eruptions (-0.5% and -0.1% respectively). Similarly, Rodriguez-Oreggia et al (2010) analyzing the case of Mexico, found that on average droughts would reduce the human development index by 1.3% while other disasters (avalanche, eruption, hailstorm, surge, snowstorm, earthquake, electric storm, tornado and strong winds) would reduce it by 1.0%. We classified the disasters in three broad categories, the third one accounting for non-natural disasters that were included in the analyses.…”
Section: Disaster Typementioning
confidence: 99%
“…This effect can return a society to the level of human development it had achieved two years prior to the disaster (Rodriguez-Oreggia et al, 2010). Indirect societal effects such as decreases in productivity in people affected by disaster can influence economic growth (Popp, 2006).…”
Section: Medium-and Long-term Socio-economic Effectsmentioning
confidence: 99%
“…For example, while flood risk reduction expenditures are counted in social cost assessment, at least part of them will, at the same time, be included positively in the calculation of GDP (EPA, 2008). Other indicators of welfare might be more appropriate For instance, RODRIGUEZ-OREGGIA et al (2012) found that there is a significant impact from natural disasters on reducing the Human Development Index (HDI) and also on increasing poverty levels. In particular, in developing countries, given their relatively high level of vulnerability, floods may have significant negative consequences.…”
Section: Indirect Tangible Costsmentioning
confidence: 99%